The study on dynamic modeling and path planning of a manta ray-inspired underwater glider - Yi Zhang; Jianing Zhang; Zhiyang Guo; Lei Zhang; Yuchen Shang; Weimin Chen (Brodogradnja)
This paper presents a biomimetic underwater glider inspired by the manta ray. Theoretical research is conducted to establish a dynamic model and address the path planning problem in gliding mode. A novel dynamic model for the gliding mode is developed, which takes the acceleration of a movable mass and the rate of change of a buoyancy control device as control inputs. Compared to previous methods, this model incorporates the real-time dynamic response of the control system, providing a more detailed depiction of the glider’s dynamic behavior. Furthermore, the steady-state equation of gliding motion within a vertical section under ocean current conditions is derived, establishing a quantitative relationship between control states and gliding steady states, which is crucial for studying gliding motion under ocean currents. Based on the dynamic model, a performance evaluation model for the glider is proposed, with evaluation metrics including energy consumption, travel time, and detection range. The path planning problem is transformed into a multi-objective optimization problem by incorporating the performance evaluation model into the research and solved using the Non-dominated Sorting Genetic Algorithm-III (NSGA-III) algorithm for different motion strategies. Numerical results demonstrate that under both ocean current and non-current conditions, the proposed path planning method can yield path parameters that meet various performance evaluation criteria and are more comprehensive, thereby validating the effectiveness of the proposed path planning approach.